The Rule of Thirds: Controlling Junction Chirality and Polarity in 3D DNA Tiles. Issue 12 (30th December 2022) - Vecchioni, Simon; Lu, Brandon; Janowski, Jordan; Woloszyn, Karol; Jonoska, Nataša; Seeman, Nadrian C.; Mao, Chengde; Ohayon, Yoel P.; Sha, Ruojie
Abstract: The successful self‐assembly of tensegrity triangle DNA crystals heralded the ability to programmably construct macroscopic crystalline nanomaterials from rationally‐designed, nanoscale components. This 3D DNA tile owes its "tensegrity" nature to its three rotationally stacked double helices locked together by the tensile winding of a center strand segmented into 7 base pair (bp) inter‐junction regions, corresponding to two‐thirds of a helical turn of DNA. All reported tensegrity triangles to date have employed ( Z + 2 / 3 ) \[\left( {Z{\bm{ + }}2{\bf /}3} \right)\] turn inter‐junction segments, yielding right‐handed, antiparallel, "J1" junctions. Here a minimal DNA triangle motif consisting of 3‐bp inter‐junction segments, or one‐third of a helical turn is reported. It is found that the minimal motif exhibits a reversed morphology with a left‐handed tertiary structure mediated by a locally‐parallel Holliday junction—the "L1" junction. This parallel junction yields a predicted helical groove matching pattern that breaks the pseudosymmetry between tile faces, and the junction morphology further suggests a folding mechanism. A Rule of Thirds by which supramolecular chirality can be programmed through inter‐junction DNA segment length is identified. These results underscore the role that global topological forces play in determining local DNA architecture and ultimately point to an under‐explored class of self‐assembling, chiral nanomaterials for topological processes in biological systems. Abstract : Designer DNA crystals from triangle tiles are self‐assembled using 7 bp (2/3 turn) and 3 bp (1/3 turn) inter‐junction segments and are analyzed by x‐ray diffraction. Triangles with 7 bp segments yielded known right‐handed, antiparallel "J1" junctions, while 3 bp triangles formed left‐handed, locally‐parallel "L1" junctions. A Rule of Thirds is elucidated that dictates tertiary chirality in 3D DNA triangles.